Antibacterial, antifungal and insecticidal activities of Ruellia tuberosa (L.) root extract (Journal of Bio-Science, 2014)
Context: Plants as therapeutics are popularized for thousands of years and people continue to rely on them for health care until now due to their effectiveness, easy availability, low cost and comparatively being devoid of serious toxic effects. Microorganisms such as bacteria, fungi and insects are developing resistance to the current therapies very easily and the currently available antibacterial, antifungal agents and pesticides are very much costly and toxic. So the current shift to the use of herbal antibacterial, antifungal agents and pesticides may be more effective, economic and advantageous. Objectives: The present research was performed to investigate the antibacterial, antifungal and insecticidal activities of the methanolic extract of the dried root of the plant Ruellia tuberosa (L.). Materials and Methods: Five Gram (+) ve bacteria namely Staphylococcus aureus, Staphylococcus agalactiae, Bacillus cereus, Bacillus megaterium, Bacillus subtilis; five Gram (-) ve bacteria namely Pseudomonus aeruginosa, Escherichia coli, Shigella flexneri, Shigella dysenteriae, Shigella sonnei were used as test bacteria for testing the antibacterial activity of the plant extract. Antifungal activity was observed against six fungi namely Candida albicans, Aspergillus niger, Aspergillus ochreus, Aspergillus ustus, Rizopus oryzae and Trichophyton rubrum. The disc diffusion assay method was used in both the cases and standard Kanamycin disc (30?g/disc) was used as the reference standard. The test for insecticidal activity was performed by using surface film activity testing method and Tribolium castaneum (Herbst) was used as the test insect. Results: The methanol extract was active against all the bacteria and fungi tested and showed significant antibacterial and antifungal properties with the zone of inhibition 9 to 23 mm for antibacterial screening and 8 to 15 mm for antifungal screening. The insecticidal assay by surface film activity test also revealed strong insecticidal activity with 80% mortality rate of Tribolium castaneum (Herbst) at a dose of 50 mg/ml in 48 hours. Conclusion: From our experiment it is informed that Ruellia tuberosa (L.) may be used to treat bacterial and fungal diseases and also as insect repellant and it is also possible to isolate antibacterial, antifungal and insecticidal drug from this plant. DOI: http://dx.doi.org/10.3329/jbs.v20i0.17720 J. bio-sci.  20:  91-97, 2012